IMPLEMENTATION OF CASH WAQAF MANAGEMENT IN ASSALAM SOCIAL INSTITUTION, JAYAPURA CITY - Mohammad Wahib (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2021)
Cash waqf has the advantage of being easy to collect because it is not constrained by the complexity of immovable waqf objects such as land and buildings. People can donate their money directly or through the transfer line in a very easy, fast and practical way. One of the organizations actively managing cash waqf in Jayapura City, Papua Province is the Assalam Social Wallet (DSA). This study describes the implementation of cash waqf management in the Assalam Social Wallet in Jayapura City. This research uses descriptive qualitative type with data collection techniques using observation and interviews. From the results of this study it is known that the response of Muslims to the cash waqf program in the Social Institution of Assalam is quite good and significant. However, the empowerment programs run by Dompet Sosial Assalam are still limited and not yet optimal, not yet leading to dynamic, innovative and varied program forms. Cash waqf funds are only used to buy land designated for the location of the Assalam foundation education. Wakaf tunai atau wakaf uang memiliki keunggulan, yaitu mudah dihimpun karena tidak terkendala dengan kerumitan benda wakaf yang tidak bergerak seperti tanah dan bangunan. Orang yang berwakaf dapat mewakafkan uangnya secara langsung atau lewat jalur transfer dengan cara yang sangat mudah, cepat dan praktis. Salah satu lembaga yang aktif mengelola wakaf tunai di Kota Jayapura Provinsi Papua adalah Dompet Sosial Assalam (DSA). Penelitian ini mendeskripsikan mengenai implementasi pengelolaan wakaf tunai di Dompet Sosial Assalam Kota Jayapura. Penelitian ini menggunakan jenis kualitatif deskriptif dengan teknik pengumpulan data menggunakan observasi dan wawancara. Dari hasil penelitian ini diketahui bahwa respon umat Islam terhadap program wakaf tunai di Dompet Sosial Assalam cukup baik dan signifikan. Namun program pemberdayaan yang dijalankan DSA masih terbatas dan belum maksimal, belum mengarah kepada bentuk program yang dinamis, inovatis dan variatif. Dana wakaf tunai hanya dimanfaatkan untuk membeli tanah yang diperuntukkan bagi lokasi pendidikan yayasan Assalam.